2021
DOI: 10.3389/fcimb.2021.769777
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio alginolyticus Triggers Inflammatory Response in Mouse Peritoneal Macrophages via Activation of NLRP3 Inflammasome

Abstract: Vibrio alginolyticus is a food-borne marine Vibrio that causes gastroenteritis, otitis media, otitis externa, and septicemia in humans. The pathogenic mechanisms of V. alginolyticus have previously been studied in aquaculture animals; however, the underlying mechanisms in mammals remain unknown. In this study, an in vitro model of mouse peritoneal macrophages infected with V. alginolyticus was established. qPCR results revealed that V. alginolyticus induced the transcription levels of various cytokines, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The HGFs in each group were scraped off and washed with PBS (C0221A; Beyotime, Shanghai, China) twice, before resuspending in caspase-1 staining solution (1:30). After 1 h of incubation in a 5% CO 2 incubator at 37°C, PI staining solution (1:100) was added to resuspend the cells [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HGFs in each group were scraped off and washed with PBS (C0221A; Beyotime, Shanghai, China) twice, before resuspending in caspase-1 staining solution (1:30). After 1 h of incubation in a 5% CO 2 incubator at 37°C, PI staining solution (1:100) was added to resuspend the cells [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein expressions of caspase-1, Capase-4, and cleaved N-terminal gasdermin D (GSDMD-N) were measured by Western blotting [ 26 ]. Proteins were extracted from cells and tissues by RIPA (Sigma-Aldrich, Missouri, USA) reagents and were detected using the BCA method (P0012; Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory response is a very complex biological process, which has an important role in many diseases ( Costa et al., 2021 ; Li et al., 2021 ; Lu et al., 2021 ; Wang J. et al., 2021 ). Previous studies showed that inflammatory response played a critical role in the onset of depression, and the disturbance of inflammation levels could increase the incidence of depression ( Leonard, 2018 ; Colasanto et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The female wild type (WT) C57BL/6 mice, TLR2-deficient (TLR2 −/− ) mice, NLRP3-deficient (NLRP3 −/− ) mice, caspase-1/11-deicient (caspase-1/11 −/− ) mice were kept in our lab, housed in the pathogen-free equipment and fed with sterile diet. The mouse peritoneal macrophages (PMs) were prepared referring to previous methods [ 17 , 18 ]. The cell purity was analysed by flow cytometry using CD11b (BioLegend).…”
Section: Methodsmentioning
confidence: 99%
“…A. hydrophila induced IL-1β release and disturbed head kidney macrophages mitochondrial dysfunction and apoptosis [ 16 ]. Moreover, IL-1β would promote TNF-α, IL-6 and IL-12 secretion to aggravate inflammation and cell death in mice macrophages infected with Vibrio alginolyticus and Vibrio harveyi [ 17 , 18 ]. However, whether A. caviae infection induces IL-1β release and the underlying molecular mechanism is needed to be further explored.…”
Section: Introductionmentioning
confidence: 99%